The Unequal Ocean : Living with Environmental Change along the Peruvian Coast - Viatori, Maximilian (Book collections on Project MUSE., 2023)
"Based on a decade of ethnographic and archival research in Peru, Life and Inequality in the Eastern Pacific reveals how dominant representations of the ocean obscure racialized disparities in the ways that different people experience the impacts of the climate crisis. In contrast, the readings offered in this book of waves and coastal development, the circulation of ocean waste, El Niño warming events, and the extraction of jumbo squid draw on experiences and ways of knowing that have been submerged by widely circulating interpretations of the Anthropocene's oceans. Life and Inequality in the Eastern Pacific presents a complex image of Peru's global seascapes as historical spaces comprised of precarious more-than-human life worlds that are tenuously arranged to expose people, non-human species, and places to unequal levels of harm. He traces how powerful actors in Peru represent the ocean through semiotic processes of translation, decontextualization, and erasure. Recognizing the significance of these processes is important for understanding not only how critical aspects of climatological and ecological crises are erased in public discourse, but also for revealing how racializing and classist discourses are inserted into discussions about climate change and environmental problems. This book also addresses expanding scholarly interest in the world's oceans as sites for thinking about social inequalities, environmental politics, and multispecies relationships"--